Sãradāmaṅgala o Sādhera āsana - Chakravarty, Biharilal, 1835-1894 (Sāhitya Prakāśa ; [bikraya Kendra: De Buka Sṭorsa, 1968)
Songs, without musical notation; includes a sketch of the life and works of the author.